Copper-Catalyzed Selective Single Arylsulfanylation of Aryl Diiodides with Aryl Thiols - Liu, Yunyun; Wang, Hang; Cao, Xiaoji; Fang, Zheng; Wan, Jie-Ping (Synthesis, 2013)
Selective single arylsulfanylation reactions of aryl diiodides with aryl or hetaryl thiols to give a broad array of iodine-functionalized sulfides were developed. Further elaboration of the iodine-containing products to provide a variety of aryl and hetaryl sulfides through coupling reactions was also demonstrated.
Keywords: copper; cross-coupling; iodides; sulfides; catalysis